Etnopedagogi IPAS Berdaya Pancasila dan Kecerdasan Buatan Sebagai Revolusi Pembelajaran Abad 21 - Beti Riasani; Ana Fitrotun Nisa; Heri Maria Zulfiati; Sutrisna Wibawa (Postgraduate, University of Mataram, 2025)
This study offers a comprehensive overview of the planning, implementation, and evaluation of innovative Science, Social, and Natural Sciences (IPAS) learning in elementary schools. The approach specifically integrates ethnopedagogy with Pancasila Education, while exploring the transformative potential of deep learning for personalized instruction. The research employed an exploratory sequential mixed-methods design, beginning with quantitative data collection and analysis, followed by qualitative data to deepen the understanding of the quantitative results. This method allowed for a holistic view of the effectiveness of IPAS learning based on ethnopedagogy and Pancasila Education, encompassing both quantitative aspects (increased interest and understanding) and qualitative aspects (implementation processes and perceptions). Key findings indicate that integrating ethnopedagogy and Pancasila Education in IPAS learning significantly increased student interest (p < 0.01) and substantially improved IPAS conceptual understanding. Furthermore, this approach strengthened the Pancasila Student Profile dimensions. Student interest showed an average increase of 26.15%, while IPAS conceptual understanding rose by an average of 20%, both with p-values less than 0.01, signifying high statistical significance. The study's uniqueness lies in its holistic mixed-methods analysis of the synergy between ethnopedagogy, IPAS, and Pancasila Education. Additionally, it offers a visionary contribution by discussing the role of deep learning in driving a 21st-century learning revolution to create adaptive and personalized learning environments. The results provide a relevant implementation model for developing 21st-century competencies and excellent student character, aiming to guide educators and policymakers.